The Conception of the Study Programme Quality Assessment and its Main Factors - Žibėrienė, Gintautė (Acta Paedagogica Vilnensia, 2006)
In the introduction of this article the problem of the research is stated and the relevance of the research to the research object, goals, main objectives, main theoretical ideas, the scientific distinction and practical value of the work are disclosed. The ontogenesis of the assessment of the quality of study is introduced. The conception of the study programme assessment is accentuated as the bridge of study programmes components which determines the coherence of these components. The quality assurance is long-life and important process, with periodical internal quality assessment and external quality assessment. The study programme assessment is very important part in this process. Countries have various experiences in study programme quality assessment area. Analysing the experience we can find different quality assessment points, criteria and indicators. What are reasons for these differences? In an article it is declared that the conception of the study programme quality assessment are swaying of four main components: study programme model; curriculum theory; national politics; philosophical aspect. All four factors do big influence on criteria’s of programme quality assessment.